Technology at the service of natural performance: cross analysis of the Oscar Pistorius and Caster Semenya cases - Issanchou, D.; Ferez, S.; de Léséleuc, E. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
Drawing from the pragmatic sociology initiated by Boltanski and Thévenot, this study bears on the moments of tension between nature`s dispositions and technology`s possibilities in sporting events. It is based on the premise that the deep meaning of sport competitions and their staging are best perceived when strange or foreign forces (an overly `bouncing` prosthesis, an overly masculine body) comes and undermines the reality tests which constitute the events. Through a cross-analysis [in the sense lent to this term by Passeron and Revel], of two athletes whose sporting achievements generated debates - Oscar Pistorius and Caster Semenya - we will underline the fundamental role of technology, which consists in instituting, in secret, reality that is always more significant from a sporting standpoint.